(untitled) (Communications in Computational Physics, 2023)
Based on the auxiliary subspace techniques, a posteriori error estimator of nonconforming weak Galerkin finite element method (WGFEM) for Stokes problem in two and three dimensions is presented. Without saturation assumption, we prove that the WGFEM approximation error is bounded by the error estimator up to an oscillation term. The computational cost of the approximation and the error problems is considered in terms of size and sparsity of the system matrix. To reduce the computational cost of the error problem, an equivalent error problem is constructed by using diagonalization techniques, which needs to solve only two diagonal linear algebraic systems corresponding to the degree of freedom (d.o.f) to get the error estimator. Numerical experiments are provided to demonstrate the effectiveness and robustness of the a posteriori error estimator.